Are Corticosteroid Injections Associated With Secondary Adrenal Insufficiency in Adults With Musculoskeletal Pain? A Systematic Review and Meta-analysis of Prospective Studies. Issue 6 (17th June 2022) - Whelan, Gareth; Sim, Julius; Smith, Benjamin; Moffatt, Maria; Littlewood, Chris
Abstract: Background: Corticosteroid injection is a common treatment for individuals experiencing musculoskeletal pain, and it is part of the management of numerous orthopaedic conditions. However, there is concern about offering corticosteroid injections for musculoskeletal pain because of the possibility of secondary adrenal insufficiency. Questions/purposes: In this systematic review and meta-analysis of prospective studies, we asked: (1) Are corticosteroid injections associated with secondary adrenal insufficiency as measured by 7-day morning serum cortisol? (2) Does this association differ depending on whether the shot was administered in the spine or the appendicular skeleton? Methods: We searched the Allied and Complementary Medicine (AMED), Embase, EmCare, MEDLINE, CINAHL, and Web of Science from inception to January 22, 2021. We retrieved 4303 unique records, of which 17 were eventually included. Study appraisal was via the Downs and Black tool, with an average quality rating of fair. A Grading of Recommendations, Assessment, Development, and Evaluations assessment was conducted with the overall certainty of evidence being low to moderate. Reflecting heterogeneity in the study estimates, a pooled random-effects estimate of cortisol levels 7 days after corticosteroid injection was calculated. Fifteen studies or subgroups (254 participants) provided appropriate estimates for statistical pooling. A total of 106 participants received a spine injection, and 148 participants received an appendicular skeleton injection, including the glenohumeral joint, subacromial bursa, trochanteric bursa, and knee. Results: Seven days after corticosteroid injection, the mean morning serum cortisol was 212 nmol/L (95% confidence interval 133 to 290), suggesting that secondary adrenal insufficiency was a possible outcome. There is a difference in the secondary adrenal insufficiency risk depending on whether the injection was in the spine or the appendicular skeleton. For spinal injection, the mean cortisol was 98 nmol/L (95% CI 48 to 149), suggesting secondary adrenal insufficiency was likely. For appendicular skeleton injection the mean cortisol was 311 nmol/L (95% CI 213 to 409) suggesting hypothalamic-pituitary-adrenal axis integrity was likely. Conclusion: Clinicians offering spinal injections should discuss the possibility of short-term secondary adrenal insufficiency with patients, and together, they can decide whether the treatment remains appropriate and whether mitigation strategies are needed. Clinicians offering appendicular skeleton injections should not limit care because of concerns about secondary adrenal insufficiency based on the best available evidence, and clinical guidelines could be reviewed accordingly. Further research is needed to understand whether age and/or sex determine risk of secondary adrenal insufficiency and what clinical impact secondary adrenal insufficiency has on patients undergoing spinal injection. Level of Evidence: Level IV, therapeutic study.